Improving early childhood pre-service teachers' computational thinking skills through the unplugged computational thinking integrated STEM approach - Ciftci, Ayse; Topcu, Mustafa Sami (Elsevier Sci Ltd, 2023)
The purpose of the current study is to investigate the effects of the unplugged computational thinking (CT) integrated STEM (UCT-STEM) approach and STEM approach on early childhood pre-service teachers' CT skills (creativity, algorithmic thinking, critical thinking, problem solving, cooperativity, communication). The study was conducted with a total of 70 early childhood pre -service teachers. Quasi-experimental design was used; activities based on the UCT-STEM approach were administered to the experimental group and activities based on the STEM approach were administered to the control group. Post-test scores for CT skills showed a statis-tically significant difference in favour of the experimental group. It was concluded that the UCT-STEM approach was more effective in developing the pre-service teachers' CT skills than the STEM approach. The current study presents an important finding to the literature in terms of the developed STEM and UCT-STEM contents and how these contents improve pre-service teachers' CT skills. The STEM and UCT-STEM content provides significant information in terms of teacher practices. At the same time, this study offers important implications for program developers and policy-makers to integrate these innovative educational approaches into both early childhood education and teacher education programs.
Keywords: Computational Thinking Skills; Computational Thinking Integrated Stem; Education; Early Childhood Pre -Service Teachers; Stem; Professional-Development